Cold Flow Behaviour of Esterified Palm Olein with TiO2 Nanoadditive for Green Lubricant - Lii Jia, Loh; Diana Kertini, Monir; Mohamad Iskandar, Jobli (Malaysian Journal of Analytical Sciences, 2025)
The poor cold flow properties of natural palm olein (POo) limits its application as a lubricant in low-temperature industrial fluids. To address this, POo was converted into large-branched esters via epoxidation, alcoholysis, and esterification. Epoxidation of POo with performic acid produced epoxidized palm olein (EPOo) with a 90.65% yield and 98.14% oxirane conversion, followed by the glycerol-based alcoholysis that incorporated three hydroxyl groups for branching at 85.93% yield. Esterification with oleic, linoleic, and salicylic acids at 140℃ for 4 h produced large-branched oleic acid-esterified palm olein (OA-EPO), linoleic acid-esterified palm olein (LA-EPO), and salicylic acid-esterified palm olein (SA-EPO) with excellent yields of 97.46%, 96.19%, and 99.29%, respectively. The Fourier Transformation Infra-Red (FTIR), proton (1H) and carbon (13C) Nuclear Magnetic Resonance (NMR) spectroscopy analysis confirmed the compound structures. The results showed significant improvement (P<0.05) in cold flow of all large-branched EPO, with pour point values ranging from -12 to -7℃ relative to POo at 6℃. SA-EPO demonstrated the lowest pour point value of -12℃ followed by LA-EPO (-11℃) and OA-EPO (-7℃). The addition of 0.1% (w/w) titanium dioxide (TiO2) nanoadditive to LA-EPO further improved its pour point from -11℃ to -12℃. These findings suggest the potential of large-branched esterified palm olein as sustainable feedstock for the development of green lubricant. By exhibiting good performance under cold condition with incorporation of nanoadditive technology, this formulation might be suitable in various sectors supporting the advancement and practical implementation of sustainable lubrication technology.